2017
DOI: 10.4081/aiua.2017.3.222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of per-operative cough stress test during transobturator mid-urethral sling surgery

Abstract: This study has been presented in EAU 2015 Meeting in Madrid.Purpose: Currently, it is unclear how the mesh tension should be adjusted on the transobturator tape surgery (TOT) for improving continence. The aim of this study was to evaluate the effects of per-operative cough stress test on TOT. Materials and methods: Between March 2007 and December 2011, 206 women with SUI were enrolled in this study. Patients were randomly categorized to treatment with TOT (96) or TOT with cough stress test (110). The IIQ-7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Ten active trial of void studies [10][11][12][16][17][18][19][20][21][22] with 1,370 patients and 16 passive trial of void studies [13][14][15][23][24][25][26][27][28][29][30][31][32][33][34][35] with 3,643 patients met inclusion criteria for passing the postoperative trial of void. Patients in the active group were significantly less likely to pass their postoperative trial of void (81%, 95% CI, 0.76-0.87% vs 89%, 95% CI, 0.84-0.93%, P5.029) with high heterogeneity (I 2 593.0%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten active trial of void studies [10][11][12][16][17][18][19][20][21][22] with 1,370 patients and 16 passive trial of void studies [13][14][15][23][24][25][26][27][28][29][30][31][32][33][34][35] with 3,643 patients met inclusion criteria for passing the postoperative trial of void. Patients in the active group were significantly less likely to pass their postoperative trial of void (81%, 95% CI, 0.76-0.87% vs 89%, 95% CI, 0.84-0.93%, P5.029) with high heterogeneity (I 2 593.0%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TOT esetén RCT során vizsgálták az intraoperatív köhögtetésteszt eredményességét a szalagfeszesség beállítása tekintetében. Akiknél az intraoperatív teszt alapján végezték a szalagfeszesség beállítását, azoknál gyakoribb volt a korai posztoperatív vizelési nehezítettség (10 vs. 2%), és a lágyéki fájdalom (10 vs. 2%), ellenben nem találtak előnyt a terápiás siker mértékében (37). Összefüggés látható a műtét hatásossága és az azt végző operatőr műtéti volumene között.…”
Section: Eredményesség Biztonságosság Szövődményekunclassified
“…Incidence of SUI is very high in female population and Jha et al demonstrated that quarter of women experienced with life quality deterioration due to SUI in their lifespan [2]. Factors affecting on SUI are still under investigation and previous reports tried to identify reasons for SUI including age, body mass index (BMI), number of births, previous gynecological surgery history, and perineal anatomic properties [3].…”
Section: Introductionmentioning
confidence: 99%